War stories : fighting, competing, imagining, leading - Hafrey, Leigh. (Giving voice to values on business ethics and corporate social responsibility collection., 2016)
Advances a leadership model for business that takes Americans beyond combat and competition as the default setting for our daily enterprise. The book draws on feature and documentary films, TV, social science, and journalism to show that in the 21st century, the United States is reaping the fruit of a long-standing and deep-rooted faith in one take on business practice. Our emphasis on competition and individual initiative has made us the standard-setters for a truly global society, but it has also resulted in a nation on a permanent war footing. That stance threatens to undermine much that we as a nation have achieved; the challenge now is to determine how we might imagine our way forward to more positive social outcomes in politics and economics at home and abroad. Rooted in the history of World War II and the Vietnam era, War Stories traces an arc of military American self-perception on the screen, the printed page, and in public conversation over the past 20 years. It juxtaposes to that arc a different, potentially more liberating and productive story, linking personal and professional commitments to organizational culture and, finally, systems thinking. Ethical, sustainable business practice depends on leaders who can tell that story of business in society, integrating public, private, and civil sector imperatives for an audience eager to engage them. War Stories ends on one such narrative, identifying the practical elements by which we can combine America's most cherished founding principles with 21st century realities.